2014
DOI: 10.1590/1516-635x1604425-430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lysine on broiler performance and carcass yield - meta-analysis

Abstract: There has been a great evolution and improvement in the nutrition of poultry and lysine has been used the reference amino acid to increase animal protein deposition. Therefore, a meta-analysis was performed with the objective of studying the effect of different dietary lysine levels on the performance and carcass yield of broiler chickens. In total, 21 studies published in Brazil since 1999 were included. Bird performance considered daily weight gain (178 observations) and feed conversion ratio (188 observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Another study reported by [24] found that the increased breast muscle yield results from high Met diets only uncovered in the fastgrowing broilers rather than in the slowgrowing broilers even though insulin-like growth factor-I (IGF-I) concentration increases in both strains of broilers. In a study reported by [25], there is a quadratic relationship (p≤0.05) between dietary lysine levels and breast meat weight. When supplementation of Met and Lys such as L or DL-methionine and lysine were not included, the fish meal might be a better choice for a moringa-corn-based diet.…”
Section: Discussionmentioning
confidence: 92%
“…Another study reported by [24] found that the increased breast muscle yield results from high Met diets only uncovered in the fastgrowing broilers rather than in the slowgrowing broilers even though insulin-like growth factor-I (IGF-I) concentration increases in both strains of broilers. In a study reported by [25], there is a quadratic relationship (p≤0.05) between dietary lysine levels and breast meat weight. When supplementation of Met and Lys such as L or DL-methionine and lysine were not included, the fish meal might be a better choice for a moringa-corn-based diet.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, the fiber sources were not analyzed for micronutrients but cassava leaf is known for its good profile in lysine (Morgan & Choct, 2016). Several studies (Ojano-Dirain & Waldroup, 2002;Adeyemi et al, 2013;Fouad & El-Senousey, 2014;Mendes et al, 2014) have confirmed the role of dietary lysine in reducing abdominal fat in broilers. Although all diluted diets were supplemented with lysine and methionine, possible beneficial effect of additional lysine from CLM may be postulated.…”
Section: Carcass Measurementsmentioning
confidence: 86%
“…Concomitantly, the role of nutrition in enabling broilers to reach their genetic potential has been widely studied, with a particular focus on AA, particularly Lys. Several studies found that increasing the level of Lys in the diet resulted in a significant increase in BW and BMY, and a significant decrease in the FCR and abdominal fat percentage (AFP) (Dozier et al, 2010;Mendes et al, 2014). More recently, variations in dietary protein or AA such as Lys during the finishing period were also found to alter breast meat pHu and associated quality traits related to their effects on breast muscle growth and carbohydrate (glycogen) content Jlali et al, 2012;Guardia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%